2020
DOI: 10.1021/jacs.9b09070
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Spirocycle Formation in the Paraherquamide Biosynthetic Pathway

Abstract: The paraherquamides are potent anthelmintic natural products with complex heptacyclic scaffolds.One key feature of these molecules is the spiro-oxindole moiety that lends a strained threedimensional architecture to these structures. The flavin monooxygenase PhqK was found to catalyze spirocycle formation through two parallel pathways in the biosynthesis of paraherquamides A and G. Two new paraherquamides (K and L) were isolated from a ΔphqK strain of Penicillium simplicissimum, and subsequent enzymatic reactio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 58 publications
2
60
0
Order By: Relevance
“…To probe the timing of spirocyclization and dioxepin ring formation, triply deuterium-labeled 7-hydroxy-25 was introduced to a culture of Penicillium fellutanum; the results indicated that indole C7 oxidation is not the immediate step following the IMDA reaction, but still may occur prior to spirooxindole formation [60]. Recent gene disruption studies in Penicillium simplicissimum established that the pyran and dioxepin rings are both formed prior to spirocyclization, elucidating two key intermediates en route to paraherquamides A (1) and G (83) [61].…”
Section: Paraherquamidesmentioning
confidence: 99%
See 3 more Smart Citations
“…To probe the timing of spirocyclization and dioxepin ring formation, triply deuterium-labeled 7-hydroxy-25 was introduced to a culture of Penicillium fellutanum; the results indicated that indole C7 oxidation is not the immediate step following the IMDA reaction, but still may occur prior to spirooxindole formation [60]. Recent gene disruption studies in Penicillium simplicissimum established that the pyran and dioxepin rings are both formed prior to spirocyclization, elucidating two key intermediates en route to paraherquamides A (1) and G (83) [61].…”
Section: Paraherquamidesmentioning
confidence: 99%
“…The PhqK flavin monooxygenase (FMO) accepts both paraherquamides K (26) and L (27) and performs a facially selective epoxidation, with a controlled collapse of the epoxide to form the spirooxindole (Fig. 2) [61]. Crystal structures revealed that substrate orientation in the PhqK active site determined the facial selectivity of epoxidation.…”
Section: Paraherquamidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Very few enzymes responsible for this type of reaction within the bicyclo-ring containing family have been characterized. [12,13] NotB catalyzes 2,3-β-face epoxidation of notoamide E (1) to generate the nonspirocyclized terminal metabolites notoamides C (2) and D (3) that do not undergo IMDA cyclization. [12] Additionally, biochemical and structural analysis of PhqK provided the first insights into the mechanism of selective spirocyclization.…”
Section: Introductionmentioning
confidence: 99%